Structure of cytochrome b (5) unique to tardigrades - Fukuda, Yohta (Protein Sci, 2020)
Cytochrome b (5) is an essential electron transfer protein, which is ubiquitously found in living systems and involved in wide variety of biological processes. Tardigrades (also known as water bears), some of which are famous for desiccation resistance, have many proteins unique to them. Here, we report spectroscopic and structural characterization of a cytochrome b (5) like protein from one of the desiccation‐tolerant tardigrades, Ramazzottius varieornatus strain YOKOZUNA‐1 (RvCytb (5)). A 1.4 Å resolution crystal structure revealed that RvCytb (5) is a new cytochrome b (5) protein specific to tardigrades.